2012
DOI: 10.1111/j.1365-2834.2012.01402.x
|View full text |Cite
|
Sign up to set email alerts
|

Strengthening communication to overcome lateral violence

Abstract: Nurse managers must raise awareness of lateral violence with individual and organizational consequences. Nursing leadership can effect organizational change to lesson lateral violence and enhance a healthy workplace culture by replicating our intervention or components of our workshops.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
71
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 25 publications
3
71
1
1
Order By: Relevance
“…This also significantly reduced incidents of verbal affronts among nurses. Because Ceravolo et al [28]'s intervention targeted all nursing staff working at hospitals, it seems possible that the effect of bullying reduction was achieved through changes in the atmosphere and organizational culture. Overall, it may be necessary to modify CRP to reflect various influencing factors and provide it at the level of the unit or entire hospital and examine its effect on both the organization and individual levels in follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This also significantly reduced incidents of verbal affronts among nurses. Because Ceravolo et al [28]'s intervention targeted all nursing staff working at hospitals, it seems possible that the effect of bullying reduction was achieved through changes in the atmosphere and organizational culture. Overall, it may be necessary to modify CRP to reflect various influencing factors and provide it at the level of the unit or entire hospital and examine its effect on both the organization and individual levels in follow-up studies.…”
Section: Discussionmentioning
confidence: 99%
“…The CRP of this study only targets individual nurses and is not considered an organizational-level intervention; as such, it likely had no organizational effects. Regarding organizational interventions, Ceravolo et al [28] aimed at enhancing awareness of bullying and self-assertive communication training with all of the nursing staff from 5 different hospitals in the US over 3 years. Nurses who took part in these workshops found that they could communicate within the nursing organization more openly, and an organizational culture of mutual respect was created.…”
Section: Discussionmentioning
confidence: 99%
“…Educational interventions such as communication workshops can positively strengthened interpersonal communication, which has been linked to creating a more respectful work environment and increased empowerment to manage future incidences of lateral violence. 13 It's important to note that exiting an unresolvable and psychologically distressing situation doesn't necessarily indicate an automatic return to baseline emotional comfort. Individuals who've experienced lateral violence and leave their jobs may experience sustained psychological distress and its manifestations in the absence of effective intervention such as guided reflection.…”
Section: Your Intervention Is Neededmentioning
confidence: 98%
“…23 The Brief T-TPQ was administered in conjunction with the final survey in a longitudinal project investigating lateral violence in nursing staff, reported in another publication. 24 The Brief T-TPQ instrument was a revision of AHRQ's 1 original T-TPQ used to measure the sustained effectiveness of TeamSTEPPS training. 25 AHRQ's 25 original 35-item survey was developed through a rigorous process of literature review, item pool creation, cognitive interviews, small group trial, and field testing.…”
Section: Measurementmentioning
confidence: 99%